Host age preference in Aphidius ervi (Hymenoptera Aphidiidae) - He, X.Z.; Wang, Q. (New Zealand Plant Protection, 2006)
Host age preference by Aphidius ervi Haliday on pea aphid Acyrthosiphon pisum (Harris) and the effects of host age on A ervi reproductive fitness and sex allocation were studied in the laboratory Aphidius ervi preferred aphids that were 35 days old over the younger (1 and 2 days old) and older (6 and 7 days old) aphids for oviposition The body size and egg load at emergence of A ervi progenies significantly increased with the increase of host age at the time of parasitisation from 1 to 4 days old after which no further increase occurred The results support the sizedependent sex ratio theory that A ervi deposits fertilised eggs in large hosts and unfertilised eggs in small ones The potential impact of the host age preference on biological control is discussed